Anti Fungi Potential of Psidium cattleianum afzel ex Sabin extraction as an inhibitor of fungi Fusarium solani - Lina Febriantini; Khotibul Umam; Putu Agus Hendra Wibawa; Wawan Sujarwo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The use of fungicides plays an important role in controlling plant diseases caused by Fusarium. However, the development of environment friendly fungicides is considered more effective, which used the plant secondary metabolites. This study aims to find the latest alternative fungicides using Psidium Cattleianum Afzel plant extract, ex Sabine from the collection of the